Psychometric properties of the 10-item Connor-Davidson Resilience Scale in Chinese military personnel - Tu, Zhihao; He, Jingwen; Wang, Ziying; Song, Mingfang; Tian, Jianquan; Wang, Chuan; Ba, Jianbo; Shen, Xinghua (Frontiers in Psychology, 2023)
Background The 10-item Connor-Davidson Resilience Scale (CD-RISC-10) is a widely used assessment of resilience. However, psychometric properties of the Chinese version of CD-RISC-10 have not been well investigated in a Chinese military personnel sample. Methods A total of 3,129 Chinese military personnel completed the CD-RISC-10, Self-rating Anxiety Scale (SAS), and Self-rating Depression Scale (SDS). Among them, 528 recruits completed the CD-RISC-10, SAS, and SDS again after 3-month basic military training (BMT). Meanwhile, the commanding officers were asked to rate recruits' training performance on the training performance rating scale for recruits (TPRS). Confirmatory factor analysis (CFA) was implemented to examine the single-factor model of the CD-RISC-10, and multigroup CFA was conducted to test measurement invariance across military rank (officers vs. enlisted), gender (male vs. female), and time (before and after 3-month BMT). Internal consistency was evaluated using Cronbach's α and McDonald's ω, and test–retest reliability was tested using the intra-class correlation coefficient (ICC). The criterion-related validity of CD-RISC was evaluated using Pearson's correlation analysis between the CD-RISC-10 total score and SAS scores, SDS scores, and training performance ratings. Results The single-factor model of the CD-RISC-10 showed adequate fit (CFI = 0.955–0.970, TLI = 0.943–0.962, RMSEA = 0.059–0.072) in all examined subsamples (male, female, officer, and enlisted), and strict invariance was also supported across military rank, gender, and time (ΔCFI ≤ 0.001, ΔTLI ≤ 0.005, ΔRMSEA ≤ 0.006). The CD-RISC-10 showed good internal consistency in all subsamples (Cronbach's α of > 0.93 and McDonald's ω of > 0.93) and good test–retest reliability (ICC = 0.88). Moreover, concurrent and predictive validity with the SAS and SDS scores were good (r = −0.68 to −0.49, p < 0.001). The resilience level of recruits at the beginning of BMT was significantly associated with training performance rated by supervisors after training (r = 0.29, p < 0.001). Conclusion The psychometric evidence reported in this study suggests that the CD-RISC-10 is a reliable and valid assessment of resilience and a potential predictor for mental health and military performance in Chinese military personnel.